2015
DOI: 10.1152/japplphysiol.00084.2015
|View full text |Cite
|
Sign up to set email alerts
|

Self-paced exercise in hot and cool conditions is associated with the maintenance of %V̇o2peak within a narrow range

Abstract: Périard JD, Racinais S. Self-paced exercise in hot and cool conditions is associated with the maintenance of %V O2peak within a narrow range. J Appl Physiol 118: 1258 -1265. First published March 26, 2015 doi:10.1152/japplphysiol.00084.2015.-This study examined the time course and extent of decrease in peak oxygen uptake (V O2peak) during self-paced exercise in HOT (35°C and 60% relative humidity) and COOL (18°C and 40% relative humidity) laboratory conditions. Ten well-trained cyclists completed four consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
57
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 47 publications
11
57
1
Order By: Relevance
“…The average heart rate during the last 10% of TTs was 185 bpm. These physiological responses are in line with previous field5 and laboratory11 studies and suggest that relative exercise intensity was likely near maximal 9. Thus the average heart rates reported in the current study are similar or slightly above those previously reported during an ITT (174 bpm)12 and TTT (165 bpm)13 in temperate environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The average heart rate during the last 10% of TTs was 185 bpm. These physiological responses are in line with previous field5 and laboratory11 studies and suggest that relative exercise intensity was likely near maximal 9. Thus the average heart rates reported in the current study are similar or slightly above those previously reported during an ITT (174 bpm)12 and TTT (165 bpm)13 in temperate environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
“…According to this premise, self‐paced exercise is regulated via positive and negative affective responses associated with the tolerance of discomfort, which influences the desire to maintain a given exercise intensity. It has recently been shown that despite reduced external workloads in response to a progressive reduction in VO 2max under heat stress and an acutely decreased VO 2max at altitude, a similar relative exercise intensity (~85%) is maintained during prolonged (~60 min) self‐paced efforts in control, hot and hypoxic conditions. This is also the approximate intensity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant development of thermal and cardiovascular strain during prolonged (i.e. >30 min) self‐paced exercise under heat stress has been shown to impair performance . Similarly, acute hypoxic exposure compromises the ability to perform time trial exercise .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…58,59). The physiological factors and/or altered perceptual clues that mediate changes in pacing strategy in the heat and subsequent adjustments following acclimatization are not well understood, but may involve integration between afferent feedback from thermal receptors, cardiovascular changes or familiarization, 60,61 but independent of the underlying mechanisms, it appears that pacing strategies are intuitively adopted by athletes in individual sports such as cycling and for team sports such as soccer 12,62 …”
Section: Introductionmentioning
confidence: 99%